ON ASYMMETRIC VOLATILITY AND STOCHASTIC VOLATILITY MODELS - Aurora, Vanessa
Volatility and forecasting volatility have become important talk among nancial practitioners as well as academia. Incorrect calculation on volatility of asset returns may lead to false risk management and capital ineciency. From academia point of view, modeling volatility is statistically challenging and its derivation may be com- plicated. Therefore, it is a need to work with and use appropriate volatility model. We explore some stylized facts of asset returns especially asymmetric behavior of returns and volatility. Firstly, we provide detailed interpretation on asymmetric property by using both real and simulation data. We then employ some common volatility models and test whether such models capture the property. It is found that EGARCH and SVAR models are among the best ones that can capture this property.